Evaluating Shared Decision-Making in Postpartum Contraceptive Counseling Using Objective Structured Clinical Examinations - Brownsyne Tucker Edmonds; Shelley M. Hoffman; Tatiana Laitano; Fatima McKenzie; Janet Panoch; Abigail Litwiller; Mark J. DiCorcia (Mary Ann Liebert, 2022)
Background: Shared decision-making (SDM) may support widespread uptake of progestin-containing long-acting reversible contraceptives in the immediate postpartum period. We piloted an Objective Structured Clinical Examination (OSCE) to evaluate first-year obstetrics and gynecology resident physicians' use of SDM in postpartum contraception counseling. Methods: As part of their 2015 and 2016 OSCEs, first-year OB/GYN residents were instructed to provide contraceptive counseling to a Standardized Patient (SP) portraying a 29-year-old postpartum patient seen during rounds on the morning following her delivery. Three investigators independently scored each resident encounter using a 10-item rubric adapted from a 9-item SDM measure and assigned scores of 0 (absent), 1 (partial), or 2 (complete). Each encounter was video and audio recorded, then transcribed for qualitative analysis. Descriptive statistics was produced using SPSS version 24. Results: Eighteen residents participated. The majority (78%) discussed contraceptive options and timing of initiation. Nearly 33% elicited factors most important to the SP in influencing her preference. Only 6% discussed the benefits of exclusive breastfeeding, and few addressed the uncertainty of progesterone on milk supply and production. Conclusion: Although residents conveyed ample clinical information, the vast majority did not discuss elements of SDM, such as her preferences, values, and goals for future fertility and breastfeeding. Our work revealed that critical elements of SDM are often not explored and deliberated by resident physicians. Trainings (e.g., OSCEs) are needed to equip residents with effective communication skills to facilitate more SDM in postpartum contraceptive care.